2020
DOI: 10.1093/icesjms/fsaa083
|View full text |Cite
|
Sign up to set email alerts
|

Surfacing and vertical behaviour of Atlantic bluefin tuna (Thunnus thynnus) in the Mediterranean Sea: implications for aerial surveys

Abstract: Atlantic bluefin tuna (Thunnus thynnus) (ABFT) frequently engage in surface basking and foraging behaviour that makes them detectable from afar. This behaviour is utilized for the development of fisheries-independent abundance indices based on aerial surveys, although changes in the surface-feeding dynamics of ABFT are not yet accounted for. We investigated the daytime surfacing behaviour of ABFT at different temporal and vertical resolutions based on 24 individuals (117–158 cm fork length), tagged with pop-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Atlantic bluefin tuna is a key commercially-important fish that is present in the GoL for most of the year (but less abundant during the spawning season (May to July) [45], with tagging studies showing site fidelity from August to October [46]. When the waters of the GoL are stratified during the summer months, bluefin tuna exploit the surface waters, where they are targeted by the longline fisheries, but as the stratification breaks down from autumn to winter, bluefin tuna move into deeper waters [46,47]. This study has shown that pelagic stingray surface daily, and data from one tag indicated that >40% of time was spent at depths of 0-2 m (Figure 3b).…”
Section: Vertical Movementsmentioning
confidence: 99%
“…Atlantic bluefin tuna is a key commercially-important fish that is present in the GoL for most of the year (but less abundant during the spawning season (May to July) [45], with tagging studies showing site fidelity from August to October [46]. When the waters of the GoL are stratified during the summer months, bluefin tuna exploit the surface waters, where they are targeted by the longline fisheries, but as the stratification breaks down from autumn to winter, bluefin tuna move into deeper waters [46,47]. This study has shown that pelagic stingray surface daily, and data from one tag indicated that >40% of time was spent at depths of 0-2 m (Figure 3b).…”
Section: Vertical Movementsmentioning
confidence: 99%
“…Atlantic bluefin tuna is a key commercially important fish that is present in the GoL for most of the year but is less abundant during the spawning season (May to July) [47], with tagging studies showing site fidelity from August to October [48]. When the waters of the GoL are stratified during the summer months, bluefin tuna exploit the surface waters, where they are targeted by the longline fisheries, but bluefin tuna move into deeper waters as the stratification breaks down in late autumn and winter [48,49]. This study has shown that pelagic stingrays surface daily, and data from one tag indicated that >40% of time was spent at depths of 0-2 m (Figure 3b).…”
Section: Vertical Movementsmentioning
confidence: 99%